2018
DOI: 10.1098/rsos.180569
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced social threat increases paranoid thinking

Abstract: The ability to attribute intentions to others is a hallmark of human social cognition but is altered in paranoia. Paranoia is the most common positive symptom of psychosis but is also present to varying degrees in the general population. Epidemiological models suggest that psychosis risk is associated with low social rank and minority status, but the causal effects of status and group affiliation on paranoid thinking remain unclear. We examined whether relative social status and perceived group affiliation, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 55 publications
7
57
2
Order By: Relevance
“…In this study, we implemented a multiple-round game theory interaction using serial dictator games. The dictator game has widely been used in paranoia research [28,29,31] and involves a situation where two participants are paired and one (the 'dictator') is given a sum of money that they can choose to share with the 'receiver' participant [32]. The receiver has no control and must accept any amount that the dictator offers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we implemented a multiple-round game theory interaction using serial dictator games. The dictator game has widely been used in paranoia research [28,29,31] and involves a situation where two participants are paired and one (the 'dictator') is given a sum of money that they can choose to share with the 'receiver' participant [32]. The receiver has no control and must accept any amount that the dictator offers.…”
Section: Introductionmentioning
confidence: 99%
“…In Study 2, we hypothesized that harmful intent attributions would be predicted by anxiety, interpersonal sensitivity and worry. Studies 1 and 2 were preregistered and included hypotheses designed to replicate findings from previous studies (high attribution of harmful intent is associated with higher paranoia and unfair dictators; [28][29][30][31]) as well as the key experimental hypotheses described above. Finally, we combined data from Studies 1 and 2 to complete exploratory analysis to gain better resolution on trial-by-trial effects, dictator exposure effects and dictator behaviour overall.…”
Section: Introductionmentioning
confidence: 99%
“…We recruited a dual online and offline sample, including a large online sample covering the population distribution of paranoid ideation, and a lab-based panels of participants who formed cohesive and non-cohesive pairs to respond to decisions made by the online participants. Previous studies have demonstrated that large-scale game theory approaches are effective in capturing live paranoid attributions and testing how paranoid attributions are modified by experimentally-induced social threat Saalfeld et al, 2018). For example, modified Dictator Games have revealed that individuals spanning the full paranoia spectrum rate unfair Dictators as intending more harm than fair Dictators, signifying that fairness is used as a threat cue irrespective of an individual's level of paranoid ideation .…”
Section: Introductionmentioning
confidence: 99%
“…For example, modified Dictator Games have revealed that individuals spanning the full paranoia spectrum rate unfair Dictators as intending more harm than fair Dictators, signifying that fairness is used as a threat cue irrespective of an individual's level of paranoid ideation . Similarly, interacting with higher status, or out-group partners also triggers exaggerated attributions of harmful intent in otherwise ambiguous interactions (Saalfeld et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Grandiose delusions involve a belief that the individual has risen in social status and has a special mission or message for the world (Knowles, McCarthy-Jones, & Rowse, 2011). Experimental studies of psychosis and the psychosis-spectrum that have examined coalitional perception and behaviour have reported alterations in the social perception of groups as paranoia increases (Greenburgh, Bell, & Raihani, 2019), an impact of in-group / out-group status on attribution of harmful intent in paranoia (Saalfeld, Ramadan, Bell, & Raihani, 2018), alterations to the social representation of others (Raihani & Bell, 2017), and a range of alterations to cooperative behaviour and emotional reactions to differences in cooperative behaviour in others accompanying delusions (Ellett, Allen-Crooks, Stevens, Wildschut, & Chadwick, 2013;Fett et al, 2012Fett et al, , 2016Gromann et al, 2013;Savulich et al, 2018).…”
mentioning
confidence: 99%